(4x+9)+(2x-12)=

Simple and best practice solution for (4x+9)+(2x-12)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x+9)+(2x-12)= equation:


Simplifying
(4x + 9) + (2x + -12) = 0

Reorder the terms:
(9 + 4x) + (2x + -12) = 0

Remove parenthesis around (9 + 4x)
9 + 4x + (2x + -12) = 0

Reorder the terms:
9 + 4x + (-12 + 2x) = 0

Remove parenthesis around (-12 + 2x)
9 + 4x + -12 + 2x = 0

Reorder the terms:
9 + -12 + 4x + 2x = 0

Combine like terms: 9 + -12 = -3
-3 + 4x + 2x = 0

Combine like terms: 4x + 2x = 6x
-3 + 6x = 0

Solving
-3 + 6x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 6x = 0 + 3

Combine like terms: -3 + 3 = 0
0 + 6x = 0 + 3
6x = 0 + 3

Combine like terms: 0 + 3 = 3
6x = 3

Divide each side by '6'.
x = 0.5

Simplifying
x = 0.5

See similar equations:

| 27x-36-14x+63=300 | | 4.5(x-9)=-25 | | 19-7m=14-6m | | 3/16-1/4 | | 5t^2+t=42 | | 2x-4(3x+1)-5= | | 3x-10+x+15=25 | | 11x-14=3x-14 | | x-1/x^3+2x | | N+17=14+3 | | -6+-12+-10+25= | | (x-3)squared=25 | | 3x^2+9=x^2+27 | | (x-3)/2=25 | | 6x^3-x^2-2x=0 | | 5x/2+12=-8 | | 5g+2g=7g | | 6-7g=-8 | | 6x+10y=50 | | x^3-9x^2+22x-15=0 | | 3n^2-5=0 | | 34-3w=25 | | 8x(8x-7)+-8x(9x-8)= | | 4-1/2 | | -50+87x=-75x^2-8x | | 8m^2+5m+4=7+3m | | 1/2*1/4 | | u+12u+17=0 | | x*x^3*x^3= | | (b^2+3b-9)/(b+5) | | 8/c+2-6=4/c+2 | | C(c+2)=12 |

Equations solver categories